Análise radiográfica das alterações periapicais e periodontais em pacientes com síndrome de sjögren primária - Braga, Paula Silva (2018)
The higher incidence of caries and periodontal impairment was described in patients with Primary Sjögren's Syndrome (SSp). As a consequence, radiolucent periapical lesions (RPL) and alveolar bone loss may occur. Despite this, LPR and radiographic alveolar bone loss were little explored in the scientific literature. This study intends to identify radiographically periapical and periodontal changes in patients with SSP. Periapical radiographs were taken for technique of parallel-cone in patients with SSp. The digital radiographs were evaluated by a radiologist through Imagine J Software. A socioeconomic questionnaire was applied. The salivary flow was evaluated through the collection of unstimulated saliva. Periapical region of all teeth, excluding third molars, was examined. In addition, alveolar bone loss was measured radiographically. Participated in the study twenty-four female patients, aged between 20 and 71 years, with xerostomia and 80% of them with hyposalivation. 70.8% of patients had at least one RPL. The mean number of teeth per patient was 23.3 ± 3.1 with prevalence of RPL in teeth of 7.86%. When comparing teeth with and without RPL, the teeth with RPL had a higher percentage root-filled teeth and tooth decay and were located more in the central superior sextant (p <0.005). For bone loss, the prevalence was 33.3%, and the pattern of horizontal bone loss prevailed (94.6%) (p <0.01). The mean age was higher for patients who presented bone loss (59.63 ± 9.14) compared to patients who did not present bone loss (49.60 ± 8.33) (p = 0.015). The horizontal bone loss was more frequent and occurred the mainly anterior region and the right inferior sextant (p <0.05). The most affected teeth were the lower lateral incisor and lower canine, followed by the lateral incisor and lower central incisor (p<0,01).When comparing with other epidemiological studies addressing healthy patients, the prevalence of RPL and alveolar bone loss was higher for patients with SSp.